Pengaruh Kualitas Produk, Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen Pada Aroma Bakery dan Cake Shop Gunung Tua - Alfauziah, Halimah Safitri; Syahriza, Rahmi; Syahbudi, Muhammad (PT. Alahyan Publisher Sukabumi, 2024)
This research aims to determine the effect of product quality, service quality and price on consumer satisfaction at Aroma Bakery & Cake Shop Gunung Tua. This research uses a descriptive quantitative approach. The number of respondents in the research was 138 people who were consumers of Aroma Bakery & Cake Shop Gunung Tua. The data analysis technique for this research uses SPSS Version 21 which includes validity and reliability tests, classical assumption tests, namely normality tests and heteroscedasticity tests, hypothesis tests with partial tests (t tests), simultaneous tests (f tests) and coefficient of determination tests (R2) and multiple linear regression analysis test. The results of this research show that product quality has a positive and significant effect on consumer satisfaction, service quality has a positive and significant effect on consumer satisfaction, price has a positive and significant effect on consumer satisfaction. Product quality, service quality and price simultaneously have a positive and significant effect on consumer satisfaction at Aroma Bakery & Cake Shop Gunung Tua. Product quality, service quality and price are the most important things in influencing consumer satisfaction. So the higher the level of each variable in influencing consumer satisfaction, the higher the consumer satisfaction will be. And if the consumer is satisfied with the product offered, the consumer will not hesitate to make a repeat purchase.